Problems of Palliative and Hospice Care in Territorial Communities as a Part of Place Branding - Anna Rosokhata; Adam Jasnikowski; Yelizaveta Yatskova; Victoriia Kurylo; Anastasiia Samoilenko (Health Economics and Management Review)
In the EU, palliative care is a comprehensive system of patient support: social, psychological, spiritual and, of course, medical care. How it works in other countries and what the experience should be applied so that children in Ukraine can not only adequately anesthetize, but also not violate their rights. These and a number of other issues and challenges today are highlighted in this study. The object of research is palliative and hospice care.The research was preceded by the following questions: to analyze current problems of palliative and hospice care in Ukraine and the world; to analyze the regulatory and legal support for palliative care in Ukraine; to study statistical data on the need for palliative and hospice care in Ukraine and local communities; to conduct a survey of residents of the united territorial communities on their awareness of palliative and hospice care and its needs in communities; develop recommendations for the implementation of modern methods of palliative care for residents of united territorial communities. The analysis examined the experience of European countries in this issue and the challenges facing Ukraine. The legal framework governing the provision of palliative care to terminally ill patients in Ukraine was analyzed. A representative survey was conducted on public awareness of the provision of palliative and hospice care to patients among the population of Sumy region. 150 respondents took part in the survey: 33% of women and 67% of men. According to the results of the research, hypotheses about the problems and needs of hospice and palliative care were confirmed. It has been found that the elderly and people with incurable diseases need it the most, and most agree that such people should be cared for in special institutions that need to be formed at the level of territorial communities. Which in turn has a significant impact on the place brand formation due to the stakeholders involvement. As a result of the study, proposals were presented to address current issues of palliative and hospice care in Ukraine, using the experience of EU countries and the implementation of it through the efforts of local communities, which in turn forms the brand of the place.